PELATIHAN PENYUSUNAN RENCANA BISNIS BERBASIS STRATEGI PEMASARAN SISWA SMK PAWYATAN DAHA 2 KEDIRI - Widyatmoko, Widyatmoko; Setiarso, Ichwan; Rahayuningtyas, Tri Esti; Himawan, Mahadika Pradipta (LPPM Universitas Nusa Mandiri, 2026)
This community service program aims to enhance the entrepreneurial competencies of students at SMK Pawyatan Daha 2 Kediri City through training in business plan development based on marketing strategies. The main problem faced by partners is students' limited understanding of how to develop comprehensive business plan components, such as market analysis, and their lack of ability to utilize information technology for digital marketing. The scope of the program includes identifying problems in business management and product marketing, developing structured business plans, and implementing digital marketing strategies using information technology. The methods employed consist of interactive training sessions, simulations, group discussions, mentoring, and business pitch presentations. Data were collected through preliminary observations, discussions with school representatives, and evaluation of students’ business plan documents as well as their digital marketing practices. The results indicate that more than 80% of participants understood the stages of business plan preparation, and approximately 70% were able to produce complete and presentation-ready business plan documents. Furthermore, over 80% of students successfully created digital promotional accounts and uploaded marketing content via social media platforms. The implementation of science and technology tools such as the Business Model Canvas (BMC), Canva, and Artificial Intelligence (AI) contributed to improved creativity, business planning effectiveness, and branding and product promotion skills. In conclusion, business plan training based on marketing strategies effectively fosters an entrepreneurial mindset, strengthens managerial and marketing skills, and prepares students to become independent and competitive young entrepreneurs.